2019
DOI: 10.1021/acs.energyfuels.8b04536
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of NiMoS Supported on (Zr)SBA-15 for Hydrodesulfurization of Diesel: Insight into a One-Step Calcination and Reduction Strategy during Sulfidation

Abstract: We report, herein, the catalytic efficiency and activity of a facilely synthesized sulfided NiMo hydrodesulfurization (HDS) catalyst supported on (Zr)-SBA-15 by one-step calcination and reduction heat treatment prior to sulfidation. Zr-SBA-15-Mo is prepared by a direct synthesis approach, followed by the confinement of Ni into the assynthesized Zr-SBA-15-Mo without calcination, to generate more dispersion and active sites of metal oxides for an efficient sulfidation process. The HDS performance of these cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Thus, Zr-containing SBA-15 has been employed as an effective support for Co to prepare Fisher-Tropsch catalysts [34,35]. In the same way, hydrodesulfurization catalysts, showing enhanced activity, have been prepared by supporting Mo, CoMo and NiMo phases on Zr-SBA-15 [36][37][38]. According to these works, the presence of Zr on the SBA-15 material provides a tunable acidity and increases the dispersion and reduction degree of the metal phases, which in turn provokes an improvement of the catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Zr-containing SBA-15 has been employed as an effective support for Co to prepare Fisher-Tropsch catalysts [34,35]. In the same way, hydrodesulfurization catalysts, showing enhanced activity, have been prepared by supporting Mo, CoMo and NiMo phases on Zr-SBA-15 [36][37][38]. According to these works, the presence of Zr on the SBA-15 material provides a tunable acidity and increases the dispersion and reduction degree of the metal phases, which in turn provokes an improvement of the catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[105][106]108 Through onestep calcination and reduction heat treatment before sulfidation, Ganiyu and Alhooshani facilely synthesized an efficient NiMo/Zr-SBA-15 catalyst, which presents better catalytic performance and stability in hydrodesulfurization of dibenzothiophene and dimethyl dibenzothiophene than those of the catalysts prepared via sequential calcination and reduction prior to sulfidation. 38 At the same time, it was found that there is a synergistic effect of Zr and Ce in the catalysts of ZrO x -CeO x -NiMo-SBA-15 applied in hydrodesulfurization since the metal sites induce a strong hydrogen bond network that leads to a higher surface stability. 109 The overall applications of zirconia-based catalysts supported on SBA-15 are summarized in Table 2 (entries 35−43).…”
Section: Zirconia Supported On Mesoporousmentioning
confidence: 99%
“…To date, zirconia-based catalysts have been involved in a variety of catalytic reactions. For instance, zirconia-based materials are regarded as one of the most promising catalysts in the industrial biodiesel production from vegetable and nonedible oils, which is a hot area for the blue print of long-lasting development of energy. The modification of zirconia can improve the acidity and accessibility of active sites on surface, enhancing the activity of zirconia-based catalysts in biofuels production. Meanwhile, the applications of zirconia-based catalysts are spread over the area of syngas production. Biomass refining reactions including dehydration, isomerization, transferhydrogenation, hydrodesulfurization, alcoholysis, hydrolysis, esterification, and etherfication are also comprehensively studied. …”
Section: Introductionmentioning
confidence: 99%
“…Different modification strategies such as addition of heteroatoms, additives, and choice of solvent have been reported . Heteroatoms that are Lewis acids such as zirconia, titania, and alumina increase the metal–support interaction from weak (which is known for silica) to moderate by increasing the acidity of SBA-15. , Different synthesis approaches have been explored to incorporate heteroatoms to SBA-15 and their effect on the catalyst HDS performance has been reported. Chelating agents such as ethylenediaminetetraacetic acid (EDTA) and citric acid have great impact on the HDS performance of the catalysts . Badoga et al studied the combined effect of EDTA and heteroatoms (Ti, Al, and Zr) on the catalytic performance of an SBA-15-supported NiMo catalyst for hydrotreating applications .…”
Section: Introductionmentioning
confidence: 99%